MANAGING DISAPPOINTMENT: REGIME SURVIVAL AND THE NORMALIZATION OF INDONESIA-UNITED STATES RELATIONS 1957-1958 - Nadhirianto, Averio (International Relations Study Program of Universitas Kristen Indonesia (UKI), 2024)
This paper examines Indonesia’s policy response during the outbreak of the rebellion of the Revolutionary Government of the Republic of Indonesia (PRRI) and the Universal Struggle Charter (Permesta) and the involvement of the United States in it. By using the omnibalancing theory, this paper aims to investigate more deeply Indonesia’s contradictory responses, which have been given special attention in previous studies. This study uses the historical study method which consist of four stages, namely heuristics, criticism, interpretation, and historiography. This study shows that the normalization path taken by Indonesia after the US involvement in the PRRI/Permesta rebellion was a tactical strategy made to ensure regime survival which was being hit by a crisis of legitimacy and threatened by state disintegration. Omnibalancing is carried out in two ways, i.e. internal balancing in the form of eradicating PRRI/Permesta elements and rearranging the political system to create Guided Democracy and external balancing in the form of normalizing relations with the United States after its intervention is publicly known. Sukarno’s omnibalancing regime then succeeded in ensuring the survival of government in power and annihilating the PRRI/Permesta while also maintaining relations with the United States.